2016
DOI: 10.1016/j.cell.2016.08.068
|View full text |Cite
|
Sign up to set email alerts
|

A Potassium-Dependent Oxygen Sensing Pathway Regulates Plant Root Hydraulics

Abstract: Aerobic organisms survive low oxygen (O2) through activation of diverse molecular, metabolic, and physiological responses. In most plants, root water permeability (in other words, hydraulic conductivity, Lpr) is downregulated under O2 deficiency. Here, we used a quantitative genetics approach in Arabidopsis to clone Hydraulic Conductivity of Root 1 (HCR1), a Raf-like MAPKKK that negatively controls Lpr. HCR1 accumulates and is functional under combined O2 limitation and potassium (K(+)) sufficiency. HCR1 regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 35 publications
(52 reference statements)
1
71
0
Order By: Relevance
“…Similarly, although Bra-botrytis-RAP2-12, Bra-botrytis-RAP2-4a , and Bra-botrytis-RAP2-10a showed fast responses to drought stress, the expression of these TFs was inhibited in the early stages of salt stress. RAP2.12 , the homologous gene of Bra-botrytis-RAP2-12 , played a vital role in anaerobic response and was involved in the root hydraulics of Arabidopsis (Gasch et al, 2016; Paul et al, 2016; Shahzad et al, 2016). RAP2.4 , the homolog of Bra-botrytis-RAP2-4a , was involved in drought stress tolerance in Arabidopsis (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although Bra-botrytis-RAP2-12, Bra-botrytis-RAP2-4a , and Bra-botrytis-RAP2-10a showed fast responses to drought stress, the expression of these TFs was inhibited in the early stages of salt stress. RAP2.12 , the homologous gene of Bra-botrytis-RAP2-12 , played a vital role in anaerobic response and was involved in the root hydraulics of Arabidopsis (Gasch et al, 2016; Paul et al, 2016; Shahzad et al, 2016). RAP2.4 , the homolog of Bra-botrytis-RAP2-4a , was involved in drought stress tolerance in Arabidopsis (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 16% of fertile land worldwide is affected by soil waterlogging, resulting in crop yield reductions of up to 80% [2]. Plants can survive in low oxygen (O 2 ) environments through the activation of diverse molecular, metabolic, and physiological responses [3], such as decreases in cellular energy change, a drop in cytoplasmic pH, enhanced aerenchyma formation, stem elongation, the use of gas films around submerged leaves, and the accumulation of toxic end-products from anaerobic respiration and reactive oxygen species (ROS) [4, 5]. Plant growth, flash and dry matter accumulation are significantly depressed by root zone oxygen deficiency [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, interactions between mineral nutrients and soil oxygen availability in the soil solution and nutrient availability (P and Fe) in a genotype are starting to emerge. Recent study demonstrated that plant root hydraulics is regulated by a potassium-dependent O 2 sensing pathway in the model plant Arabidopsis thaliana [17]. A molecular pathway involving Hydraulic Conductivity of Root 1 and the transcription factor RAP2 was proposed as a relevant target for improving the resilience of plants to flooding.…”
Section: Discussionmentioning
confidence: 99%